Charakterystyka profilu kandydata do samodzielnego prowadzenia ksiąg rachunkowych (na podstawie studium podyplomowego "Rachunkowość i kontrola finansowa" lata 2000-2004) - Biernacki, Michał; Rogowski, Wojciech (Profile Description of the Accountant Candidate (Based on the Postgraduate Study "Accounting and Financial Control" Years 2000-2004), 2005)
In this article are presented results of the research on profile description of the accountant candidate, based on the survey from postgraduate study "Accounting and Financial Control" organized by Accountants Association in Poland and Chair of Financial Accounting and Control. Basing on the results, it is possible to state that people who are competing for an accounting certificate are mostly: women, young adults, very often soon after getting master degree in economics, or in law majors, people who do not have or have only two or three years of experience as an independent accountant or in economic-financial branch, where they are using accounting knowledge.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1079, s. 25-34